RELEVANSI MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PPKN SISWA SEKOLAH DASAR - Agustinus Jeharum; Laurentius Ni; Rudolof Ngalu (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
The quality of elementary schools is determined, one of which is student learning outcomes, both academically, affectively, and psychomotor. The facts reveal that the low learning outcomes of Civics in elementary schools is the most common problem. The causes include the use of learning methods that are not in accordance with the characteristics of the material, students, and learning objectives. This study aims to describe the use of the CTL method in improving Civics learning outcomes for elementary school students. The writing method used a literature review by tracing library sources. The results of the study show that CTL can improve student Civics learning outcomes. This can be seen from various facts and research findings that support the effectiveness of the CTL method. Its uses include where students are invited to find out for themselves the material that occurs in close relationship with actual experience.